PENGARUH PENGGUNAAN QRIS DAN PROMOSI DIGITAL TERHADAP PENINGKATAN PENJUALAN PADA TOKO PAKAIAN TRENDZ STORE RANTAUPRAPAT - Rina Fronica Siregar; Sri Ayla; Nurhabibah Ritonga (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze the effect of using QRIS and digital promotion on increasing sales at Trendz Store Rantauprapat, a modern clothing store that actively adopts technology in its business operations. The method used is descriptive with a quantitative approach through observation, interviews, and sales data before and after the implementation of QRIS and digital promotions. The results show that the use of QRIS facilitates transactions and increases customer convenience, while digital promotions through social media are effective in attracting new consumers and increasing the loyalty of existing customers. The synergy between the two has a significant impact on increasing sales of Trendz Rantauprapat stores with a joint effect of 40.3%. Therefore, the integration of digital payment technology and online marketing strategies is an important factor in the development of retail businesses in today's digital era.